Active control of compressible channel flow up to Mab=3 using direct numerical simulations with spanwise velocity modulation at the walls. Issue 1 (11th January 2022) - Ruby, Marius; Foysi, Holger
Abstract: Active turbulence control has been pursued continuously for the last decades, striving for an altered, energetically more favorable flow. In this article, our focus is on a promising method inducing a spanwise wall movement in order to reduce turbulence intensity and hence friction drag, investigated by means of direct numerical simulation. This approach transforms a previously time dependent oscillatory wall motion into a static spatial modulation with prescribed wavelength in the streamwise direction [48]. Most procedures related to turbulence control including the present one have been overwhelmingly applied to incompressible flow. This work is different and novel to the effect, that this control method is applied to compressible, supersonic channel flow up to a bulk Mach number of M a = 3 . Due to substantial variations of viscosity, density, and temperature within the near‐wall region in supersonic flow, the impact of the control method is altered compared to solenoidal flow conditions. By creating a data set of different Mach‐/Reynolds numbers and control parameters, knowledge is gained in which way the effectiveness of oscillatory techniques and physical mechanisms change under the influence of compressibility. It is shown that the control method is able to effectively reduce turbulence levels and lead to large drag reduction levels in compressible supersonic flow. Variable property effects even enhance this behavior for the whole set of investigated parameters. Overall, the higher Mach number cases show a larger net power saving compared to the incompressible ones. Furthermore, we observe an increase of the optimum wavelength with increasing Mach number, which helps in guiding optimal implementations of such a control method.